2010
DOI: 10.1007/s10333-009-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial rootzone drying on yield, yield components, and irrigation water use efficiency of canola (Brassica napus L.)

Abstract: Effect of PRD (partial rootzone drying) on yield and yield components of canola (Brassica napus L.) was investigated in greenhouse conditions. The treatments were: T 1 , full watering of both sides of roots; T 2 , alternate irrigation on both sides; T 3 , half of irrigation water in T 1 was given to one side; T 4 , same as T 3 but without plate; T 5 , same as T 2 but without plate. In T 1 , T 2 , and T 3 treatments, the boxes were evenly separated into two compartments with thin plates. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…IWUE varied with year, with no correlation between IWUE and the seasonal irrigation amounts. The results of this study are in agreement with Mousavi et al [60], who reported that the IWUE for winter canola varied from 0.36 kg/m 3 for the least efficient irrigation regime to 0.67 kg/m 3 for the most efficient irrigation regime, under greenhouse conditions. Majnooni-Heris et al [61] reported spring canola IWUE values varying from 0.36 to 0.43 kg/m 3 under different irrigation regimes at the Agriculture and Natural Resources Research Center of Yazd city, Iran.…”
Section: Winter Canola Irrigation Water and Crop Water Use Efficiencysupporting
confidence: 93%
“…IWUE varied with year, with no correlation between IWUE and the seasonal irrigation amounts. The results of this study are in agreement with Mousavi et al [60], who reported that the IWUE for winter canola varied from 0.36 kg/m 3 for the least efficient irrigation regime to 0.67 kg/m 3 for the most efficient irrigation regime, under greenhouse conditions. Majnooni-Heris et al [61] reported spring canola IWUE values varying from 0.36 to 0.43 kg/m 3 under different irrigation regimes at the Agriculture and Natural Resources Research Center of Yazd city, Iran.…”
Section: Winter Canola Irrigation Water and Crop Water Use Efficiencysupporting
confidence: 93%
“…The use of APRI has been reported for many crops (e.g. maize, tomatoes, cotton and grapes) (Intrigliolo & Castel, ; Li, Yu, Nong, Kang, & Zhang, ; Mousavi, Soltani‐Gerdefaramarzi, & Mostafazadeh‐Fard, ; Wang, Liu, Mathiasn, & Christianr, ). Furthermore, previous reports have shown that APRI can reduce irrigation water consumption and stimulate soil water lateral flow, thereby decreasing N leaching and enhancing crop N uptake (Li et al, ; Li, Zhang, & Jia, ; Skinner, Hanson, & Benjamin, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…3B). Mousavi et al (2010) also reported maximum height in alternate PRD treatment among five irrigation treatments for canola (Brassica napus L.) plants. The plant height differences within treatments and growing seasons were not significant (P # 0.05) during both growing seasons ( Fig.…”
Section: Resultsmentioning
confidence: 96%